UNLOCKING THE POTENTIAL OF DATA ANALYTICS TO SUPPORT ACCOUNTING EDUCATION PEDAGOGY IN SOUTH AFRICAN SECONDARY SCHOOLS - Sithole, Nosihle Veronica; Schlebusch, Carlie Luzaan (Faculty of Administrative Science, Universitas Brawijaya, 2026)
This study aims to explore how data analytics can be leveraged to improve accounting teaching for Grade 12 learners in South Africa. In the digital era, data analytics has emerged as a transformative tool in education, yet its application in supporting accounting teaching at secondary school level remains underexplored. In South Africa, Grade 12 learners continue to encounter difficulties in mastering accounting concepts due to traditional, theory-heavy teaching approaches that often lack interactivity and real-world relevance. Despite the growing importance of data literacy in the accounting profession, a significant gap exists in the integration of data analytics into classroom instruction to enhance learners’ engagement, understanding, and performance. A mixed-method research approach was adopted, sampling accounting teachers across selected schools in Lejweleputswa district. Data was collected through surveys and semi-structured interviews. The study first gathered data on teachers’ current use of data analytics in accounting and then explored its potential to support accounting pedagogy. Findings indicate that accounting teachers currently make limited use of data analytics in their teaching. However, teachers expressed positive perceptions regarding its personalisation of accounting learning through data analytics, improvement of assessment accuracy, promotion of problem-solving skills and critical thinking, enhanced engagement and motivation towards accounting subject. Based on these findings, the study recommends targeted professional development programmes for teachers in educational data analytics, investment in ICT infrastructure, and the inclusion of data literacy components in the secondary accounting curriculum. The study concludes that unlocking the potential of data analytics in accounting education is both timely and essential for aligning school pedagogies with 21st-century accounting practices. Strategic integration of data analytics can foster deeper conceptual understanding, bridge the gap between theory and practical learning, and enhance learner performance in accounting.